Negative Constructions in Mapudungun: A Typological Approach - Olate, Aldo (2020)
In this paper, we explore the negative constructions in Mapudungun from the perspective of current linguistic typology. Based on published sources and fieldwork data, we establish the prototypical negative schemes and their variation in Mapudungun. We propose a typological classification of the constructions in agreement with the standard negation, negatives pronouns, and the types of mechanism that the language has for expressing the negation. Finally, surveyed and advance some general reflections on this phenomenon in the language.